2004
DOI: 10.1002/ajh.20092
|View full text |Cite
|
Sign up to set email alerts
|

Detection of hepatitis C virus RNA in paraffin‐embedded tissues from patients with non‐Hodgkin's lymphoma

Abstract: The aim of this study is to detect the possible role of hepatitis C Virus (HCV) in lymphomagenesis. HCV‐RNA and anti‐HCV antibodies were studied in tissue and serum samples taken from patients with non‐Hodgkin's Lymphoma (NHL). The prevalence of HCV, the clinical presentation of these cases, and association with histologic subtypes were determined. RT‐PCR was used to detect the HCV‐RNA in serum and tissue samples. The anti‐HCV antibodies were tested with microparticle enzyme immunoassay. Immunohistochemistry w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 47 publications
(38 reference statements)
1
17
0
Order By: Relevance
“…They found that 51.7% of the 29 cases of splenic DLB were HCV-Ab-positive, and found the HCV RNA genome in lymphoma tissue in six of the seven cases examined, and the expression of NS3 protein and E2 protein in cell cytoplasm in five of the seven cases (as in our case) [15]. Moreover, Paydas et al reported that the HCV RNA genome was detected in 37% of 30 cases of NHL (including 15 cases of DLB) and that the serum level of HCV RNA was high in 23.3% of the cases [16]. There have also been several other studies on the expression of HCV NS3 protein and E2 protein, and the detection of the HCV RNA genome in lymphoma tissues [8,17,18], and the results of those studies also suggest a strong association between NHL and HCV infection.…”
Section: Discussionsupporting
confidence: 45%
“…They found that 51.7% of the 29 cases of splenic DLB were HCV-Ab-positive, and found the HCV RNA genome in lymphoma tissue in six of the seven cases examined, and the expression of NS3 protein and E2 protein in cell cytoplasm in five of the seven cases (as in our case) [15]. Moreover, Paydas et al reported that the HCV RNA genome was detected in 37% of 30 cases of NHL (including 15 cases of DLB) and that the serum level of HCV RNA was high in 23.3% of the cases [16]. There have also been several other studies on the expression of HCV NS3 protein and E2 protein, and the detection of the HCV RNA genome in lymphoma tissues [8,17,18], and the results of those studies also suggest a strong association between NHL and HCV infection.…”
Section: Discussionsupporting
confidence: 45%
“…Various viral and environmental factors are held responsible for the development of NHL (Barista et al, 1994;Paydas et al, 2004). Spinelli et al investigated the relationship between the serum organochlorine levels and NHL.…”
Section: Discussionmentioning
confidence: 99%
“…The infection of HCV results in a higher rate of chronic infection compared to HBV infection with approximately 80% of infected subjects showing viral persistence and chronic liver diseases [5,6], thus an accurate diagnosis is essential to identify the presence of HCV RNA in apparently symptom free carriers [7,8]. Patients with HCV infection develop chronic liver disease, in this group, about 30% progress to cirrhosis, and 1-2% develops hepatocellular carcinoma per year [9,10].…”
Section: Introductionmentioning
confidence: 99%